Professional HTML5 mobile game development - Rettig, Pascal K. (WIley Pub. Inc., 2012)
Create mobile game apps for the lucrative gaming market If you're an experienced developer seeking to break into the sizzling mobile game market, this is the book for you. Covering all mobile and touchscreen devices, including iPhones, iPads, Android, and WP7.5, this book takes you through the steps of building both single- and multi-player mobile games. Topics include standard patterns for building games in HTML5, what methods to choose for building (CSS3, SVG, or Canvas), popular game engines and frameworks, and much more. Best of all, code for six basic games is provided, so you can modify.